Value Functions for Infinite-Period Planning - Harvey, Charles M. (Management Science, 1986)
Cost-benefit and risk analysis studies that model tradeoffs between the present and the distant future by means of present value discounting have been criticized for according the future, and thus future generations, far too little importance. This paper presents an alternative means of modeling tradeoffs between different periods that accords the future far more importance than present value discounting, and that is no more difficult to apply. The paper also presents a means of modeling the preference issue of concern for equity or stability between different periods.